Cytogenetic response to prior treatment with interferon-α is predictive for survival after allogeneic hematopoietic stem cell transplantation in chronic myeloid leukemia - Maywald, Ole; Pfirrmann, M.; Berger, Ute; Breitscheidel, L.; Gratwohl, A.; Kolb, H.-J.; Beelen, D. W.; Tobler, A.; Metzgeroth, Georgia; Gnad, S. U.; Hochhaus, Andreas; Hasford, J.; et al. (Leukemia, 2006)
We investigated the impact of a cytogenetic response (CyR) to IFN prior to and at the time of allogeneic hematopoietic stem cell transplantation (HSCT) on transplant-related mortality (TRM), relapse rate and survival probability after HSCT in 162 transplanted patients with chronic myeloid leukemia. One-hundred-one patients (62.3%) achieved a CyR prior to HSCT. Survival probabilities were higher in patients, who achieved any CyR prior to HSCT than in patients without CyR (63.6 vs 49.2%: P=0.019). Survival probabilities in patients, who achieved a major CyR were better than in patients with minimal and minor CyR or in patients with no CyR (69.4 vs 58.8% vs 49.2%: P=0.040). TRM and survival of chronic phase patients without CyR at the time of HSCT were similar to that of patients transplanted in advanced phase. Both groups combined had an outcome inferior to patients with at least minimal CyR (TRM, Gray test: P=0.016, survival, log-rank test: P=0.002). Univariate and multivariate analyses identified CyR prior to or at HSCT as a strong and independently favorable prognostic factor. We therefore conclude that allogeneic HSCT in CyR should be investigated prospectively as an alternative treatment option in defined patient groups.